1993
DOI: 10.1007/bf01142931
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional parameters of left ventricular performance in healthy subjects during rest and exercise assessed by radionuclide ventriculography

Abstract: The aim of our study was to analyze numerous global and regional parameters of left ventricular (LV) performance during rest and exercise, in the group of 14 healthy subjects, by quantitative gated equilibrium ventriculography in left anterior oblique view (45 degrees). The global LV parameters at rest vs. exercise in our study were: heart rate 68.9 +/- 18.4 vs. 137.5 +/- 38.6; systolic blood pressure (mmHg) 121.8 +/- 18.2 vs. 178.6 +/- 31.2; diastolic blood pressure (mmHg) 82.1 +/- 10.8 vs. 90.7 +/- 12.4; dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
1
1
Order By: Relevance
“…It is of importance to note that peak emptying rate at rest was higher than peak filling rate in both runners and controls contrasting to what is previously reported in normal subjects ( Bergovec et al . 1993 ).…”
Section: Discussioncontrasting
confidence: 96%
“…It is of importance to note that peak emptying rate at rest was higher than peak filling rate in both runners and controls contrasting to what is previously reported in normal subjects ( Bergovec et al . 1993 ).…”
Section: Discussioncontrasting
confidence: 96%
“…The fact that the right and left SV did not increase significantly during exercise was consistent with the work of Belever et al on adaptations of the heart during exercise in the supine position [42]. However, Bergovec et al showed a significant increase in end diastolic volume and SV of the LV during exercise by radionuclide ventriculography [43]. More recent work by Stöhr et al [44] confirmed that the SV increases early, at the beginning of the exercise, before reaching a plateau, after which the increase of CO is only related to the higher heart rate.…”
Section: Discussionsupporting
confidence: 82%
“…4 Up to one third of acute myocardial infarctions can be clinically silent; 36,37 up to 30% of acute myocardial infarctions never manifest diagnostic Q waves; a diagnostic Q wave disappears in 10% to 30% of Q-wave infarctions 38 or is not diagnostic 2 years after an acute myocardial infarction. 39 Therefore, silent ischemia or myocardial infarction or chronic ischemia/hibernating myocardium may cause WM abnormalities at rest. Although mild hypokinesis may be a normal variant, 40 hypokinesis is strongly associated with significant CHD.…”
Section: Discussionmentioning
confidence: 99%